Detection of paranasal ectopic adrenocorticotropic hormone‐secreting pituitary adenoma by Ga‐68‐DOTANOC positron‐emission tomography–computed tomography. (8th January 2013) - Veit, Johannes A.; Boehm, Bernhard; Luster, Markus; Scheuerle, Angelika; Rotter, Nicole; Rettinger, Gerhard; Scheithauer, Marc
Abstract : Ectopic adrenocorticotropic hormone (ACTH)‐secreting tumors account for approximately 10% of Cushing's syndrome (CS). We present an extremely rare case of a patient with CS caused by an ectopic ACTH‐secreting pituitary adenoma (EAPA) of the ethmoid sinus. The tumor was identified by positron‐emission tomography–computed tomography (PET/CT) using the somatostatin receptor analogue Ga‐68‐DOTANOC. Transnasal endoscopic resection was performed and the patient showed significant clinical improvement with normalization of the endocrine pituitary axis. Immunostaining showed a somatostatin receptor 2 and 5‐positive ACTH‐producing adenoma. In patients with ectopic ACTH secretion, Ga‐68‐DOTANOC‐PET/CT may play an important role in the localization of EAPA. Transnasal endoscopic resection is the therapy of choice.